Anti-corrosion self-repairing epoxy composite coating and preparation method thereof
By preparing the combination of core-shell composite particle ternary materials and epoxy resin, the existing coating technology has solved the problem of structural instability and poor corrosion resistance in high-salt environments, and achieved efficient anti-corrosion and self-repair effects.
Patent Information
- Application Number
- CN202510190535.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing coating technology has unstable structure and vulnerable components in high-salt environments, weak mechanical strength and adhesion, and is susceptible to electrochemical corrosion caused by dielectric corrosion, affecting corrosion resistance.
By preparing core-shell composite particle ternary materials, including covalent organic framework materials, benzotriazole and nanomoS2, combined with epoxy resin, curing agent and catalyst, an anti-corrosion self-healing epoxy composite coating is formed. This coating can effectively seal corrosive media in a high-salt environment, improving the density and corrosion resistance of the coating.
It achieves improving the corrosion resistance and self-repairing performance of the coating in a high-salt environment, extending the service life of the coating, and reducing production costs.
Smart Images

Figure CN119875472A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional coating development, and relates to an anti-corrosion self-repairing epoxy composite coating and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand, oil, as one of the important fossil energy sources, occupies a pivotal position in the energy structure. In the current oil injection pipe anti-corrosion, epoxy anti-corrosion coating technology in organic coating anti-corrosion technology is widely used in the field of oil field water injection development. However, in the process of deep well and ultra-deep well development, affected by the high-salt corrosive environment, the structure of traditional anti-corrosion coating is unstable, the organic components in the coating decompose and oxidize quickly, and at the same time, the mechanical strength and adhesion of the coating are weak, resulting in cracks and even peeling of the coating. The high-salt environment will aggravate the flow of chloride ions, water, gas and other media into the coating, forming a corrosive medium, and forming an anode area and a cathode area at the coating / metal interface for electrochemical corrosion. The anti-corrosion performance of the coating is greatly reduced. As a result, the corrosion resistance of the water injection pipe column is reduced, posing a threat to the normal production and long-term stable development of the oil field.
[0003] At present, people have developed many anti-corrosion methods, among which the anti-corrosion self-healing coating technology has the advantages of low cost, high efficiency and wide application range, and is an ideal anti-corrosion strategy. Chinese patent CN202011616153.0 provides "a filler loaded with MOF corrosion inhibitor, a self-healing anti-corrosion coating and its preparation method", which encapsulates the corrosion inhibitor in the capsule of the organic skeleton compound MOF assembled by two organic multi-dentate ligands, can react with the metal substrate, enhance the adhesion and anti-corrosion performance with the substrate, and has a high self-healing function. However, since the skeleton structure of MOF is easy to collapse under harsh conditions such as high temperature and high pressure, the stability and service life of its coating are poor. Chinese patent CN201810896499.7 provides "a molybdenum disulfide anti-corrosion coating and its preparation method", which adds molybdenum disulfide anti-corrosion coating to an acrylic resin / epoxy resin mixture to obtain a coating with good anti-corrosion and mechanical properties. The curing temperature of epoxy resin is higher than that of acrylic polyurethane. Long-term use will affect the stability of the entire system. Chinese patent CN202410819012.0 discloses "a high-strength anti-corrosion coating for oil casing and its preparation method", which improves the anti-corrosion performance of the coating by adding modified graphene to the hollow nickel alloy, increases the contact surface between the coating and the environment, and enhances the reaction activity and catalytic performance. Since graphene reacts with air under high temperature conditions and is expensive, the stability and applicability of the coating are greatly reduced. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides an anti-corrosion self-repairing epoxy composite coating and a preparation method thereof, thereby solving the technical problems in the prior art that the existing coating technology is unstable in structure, has fragile components, has weak mechanical strength and adhesion, is easily corroded by the medium and causes electrochemical corrosion, and affects the corrosion resistance.
[0005] The present invention is achieved through the following technical solutions: A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: S1: adding 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to a mixed solution of 1,4-dioxane, n-butanol and methanol, and reacting to obtain a covalent organic framework material; dispersing a benzotriazole solution and the covalent organic framework material into a solvent, vacuum loading, and centrifuging to obtain a core-shell composite particle binary material; S2: dispersing the core-shell composite particle binary material in water, adding nano-MoS2 sheets to modify its surface, and preparing a core-shell composite particle ternary material; S3: Mix the core-shell composite particle ternary material with a curing agent and a catalyst, add the mixture into epoxy resin, stir evenly, and obtain the anti-corrosion self-repairing epoxy composite coating.
[0006] Preferably, in step S1, the ratio of 1,3,5-tris(4-aminophenyl)benzene to 2,5-dimethoxyterephthalaldehyde is (1-2):(0.5-1.6) by mass.
[0007] Preferably, in step S1, the ratio of 1,4-dioxane, n-butanol and methanol is (20-100):(20-100):(0.2-1) by mass.
[0008] Preferably, the cavity diameter of the covalent organic framework material is 450-1300 nm, and the surface pore diameter is 2-26.5 nm.
[0009] Preferably, in step S1, the ratio of the benzotriazole solution to the covalent organic framework material is (0.01-0.1):(0.1-5) by mass.
[0010] Preferably, in step S2, the diameter of the nano MoS2 sheet is 1000~1500nm and the thickness is 20~30nm.
[0011] Preferably, in step S2, the ratio of the nano-MoS2 sheets to the core-shell composite particle binary material is (1-10):(1-10) by mass.
[0012] Preferably, in step S3, the ratio of the core-shell composite particle ternary material, the curing agent, the catalyst and the epoxy resin is (3-10):(8-16):(0.02-0.04):(10-20) by mass.
[0013] An anti-corrosion self-repairing epoxy composite coating is prepared by the above method.
[0014] A corrosion-resistant self-repairing epoxy composite coating, which is obtained by coating the above-mentioned corrosion-resistant self-repairing epoxy composite coating on the surface of a substrate and curing it; the thickness of the corrosion-resistant self-repairing epoxy composite coating is 95-105 μm; the adhesion of the corrosion-resistant self-repairing epoxy composite coating is less than level 1, the wear resistance strength is greater than 1000 HV, and the wear resistance is greater than 5.0 L·um -1 In a NaCl concentration of 3.5 wt.%, the salt spray resistance time is greater than 1400 h, and the self-repairing efficiency of the anti-corrosion self-repairing epoxy composite coating is greater than 90%.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a method for preparing an anti-corrosion self-repairing epoxy composite coating, firstly preparing a spherical amino-containing covalent organic framework material (PZ-COFs), adding a benzotriazole (BTA) solution to carry out a self-assembly reaction to prepare a core-shell type composite particle binary material (PZ-COFs / BTA), then using a nano MoS2 sheet to modify the surface of the material to prepare a core-shell type composite particle ternary material (PZ-COFs / BTA@MoS2), finally mixing the core-shell type composite particle ternary material with a curing agent and a catalyst, and adding an epoxy resin (Epoxy Resin, EP), stirred evenly, and the anti-corrosion self-healing epoxy composite coating (PZ-COFs / BTA@MoS2 / EP) was obtained. The whole preparation process was simple and could be produced continuously. The two-dimensional layered material MoS2 flakes in the material had unique layered barrier effect, ultra-high specific surface area and excellent physical and mechanical properties. When added to the epoxy coating, due to its unique layered barrier effect and ultra-high specific surface area, the defects of the coating caused by curing can be sealed, the density of the coating can be improved, and the corrosive media such as chloride ions, water and gas can be blocked from flowing into the coating in a high-salt environment, thereby slowing down corrosion and effectively improving the corrosion resistance of the coating. MoS2 had stable chemical properties, could adapt to high-temperature working environment, and was more stable and durable. At the same time, MoS2 had physical and mechanical properties, had high adhesion to the substrate, could reduce friction and wear, thereby extending the service life of the coating and improving performance. Two-dimensional covalent organic framework materials (PZ-COFs) have the advantages of low density, high specific surface area, easy modification and functionalization. The end-capped amino groups can react with epoxy to promote the curing of epoxy. They can also reduce the contact area between the material and the environment, and have the function of blocking and shielding corrosive media, thereby effectively improving the corrosion resistance of the coating. At the same time, MoS2 can be used as a carrier of PZ-COFs and can enhance the mechanical properties of the material, improve the strength and toughness of the material, and further improve the overall strength of the anti-corrosion coating. In addition, the surface modification of MoS2 using PZ-COFs can effectively improve the compatibility and dispersibility of MoS2 in epoxy resin. The corrosion inhibitor benzotriazole solution (BTA) is compounded into PZ-COFs@MoS2 through a self-assembly method, which not only delays the penetration of the corrosive medium into the substrate; but also enables the corrosion inhibitor BTA to adhere to the surface of the metal substrate more effectively and stably to form a protective film, exert its own corrosion inhibition effect, and prevent further corrosion of the substrate; and when the coating surface is damaged and the environmental pH changes, BTA can spontaneously flow out to form a protective film with self-repairing properties, thereby preventing further corrosion.Compared with the defects of traditional epoxy resin coatings, which have complex preparation processes, harsh repair conditions, and cannot take into account both anti-corrosion performance and self-repairing performance, the present invention provides an anti-corrosion self-repairing epoxy composite coating having the advantages of unique layered barrier effect, ultra-high specific surface area, high stability and excellent physical and mechanical properties, which can effectively solve the above problems. The anti-corrosion self-repairing epoxy composite coating provided by the present invention has a simple entire preparation process and can be applied to various fields such as oil pipelines, ships, energy industry, emerging marine engineering and construction.
[0016] Furthermore, in step S1, the ratio of 1,3,5-tris(4-aminophenyl)benzene (TAPB) to 2,5-dimethoxyterephthalaldehyde (DMTP) is (0.1-1):(0.1-1) by weight, which is conducive to the Schiff base reaction between the amino group in TAPB and the aldehyde group in DMTP, thereby forming a dynamic imine bond to obtain the target product PZ-COFs. The introduction of 1,3,5-tris(4-aminophenyl)benzene enhances the overall stability of the PZ-COFs material by forming a more stable covalent bond structure, and this stability is conducive to improving the corrosion resistance and self-healing properties of the material; DMTP, as part of the building block of the PZ-COFs material, reacts to form a stable covalent bond to connect multiple molecules together, constructing a PZ-COFs material with a specific pore structure and chemical stability; secondly, the mixing of an appropriate amount of TAPB and DMTP can increase the crosslinking density without significantly reducing the original performance of DMTP, which helps to improve the mechanical strength, heat resistance and corrosion resistance of the material.
[0017] In step S1, the ratio of 1,4-dioxane, n-butanol and methanol is (20~100):(20~100):(0.2~1) by mass. 1,4-dioxane and n-butanol are used as co-solvents. The polarity of the reaction system can be adjusted and the reaction conditions can be optimized by the combined action of 1,4-dioxane and n-butanol. Methanol is used as a precipitant and solvent. By adjusting its ratio in the reaction system, the precipitation and crystallization process of the COFs material can be controlled, thereby affecting the structure and properties of the COFs material.
[0018] Preferably, in step S1, the cavity diameter of the covalent organic framework material (PZ-COFs) is 450~1300nm, and the surface pore size is 2~26.5nm. The cavity diameter of PZ-COFs is larger, which is conducive to coating more corrosion inhibitor BTA, which can not only delay the penetration of the corrosive medium into the substrate, but also make the corrosion inhibitor BTA more effectively and stably attached to the surface of the metal substrate; the surface pore size is 2~26.5nm, the pore size is larger, the outflow rate of BTA is increased, and when the coating surface is damaged and the environmental pH changes, BTA can flow out quickly to form a protective film with high self-repairing performance.
[0019] Preferably, in step S1, the ratio of the benzotriazole solution to the covalent organic framework material is (0.01-0.1):(0.1-5) by weight. If too little benzotriazole solution (BTA) is added, BTA is easy to flow out in the subsequent preparation process, which is not conducive to increasing the sustained-release function of the coating, and the self-repair and corrosion resistance are not high. If too much BTA is added, on the one hand, the amount of BTA embedded in PZ-COFs is limited, which wastes raw materials. On the other hand, too much BTA is embedded in PZ-COFs, which is not conducive to the outflow of BTA. When the coating is damaged, the outflow rate of BTA is very small, resulting in a weakened self-repair ability of the coating, which further leads to a weakened corrosion resistance of the coating.
[0020] Furthermore, in step S2, the diameter of the nano MoS2 sheet is 1000~1500nm, and the thickness is 20~30nm. Firstly, the smaller the diameter of the nano molybdenum dioxide, the larger its specific surface area. The increase in specific surface area is conducive to improving the reactivity and adsorption capacity of the material, so that it can combine with more surface modifiers; secondly, the small particle size and good dispersibility of the nano molybdenum dioxide are conducive to its uniform mixing with other materials, thereby improving the overall performance of the composite material; thirdly, the nano molybdenum dioxide is thinner and lighter, which is conducive to the adhesion of molybdenum disulfide to the metal surface, thereby increasing the stability of the coating.
[0021] Furthermore, in step S2, the ratio of the nano-MoS2 sheets to the core-shell composite particle binary material is (1~10):(1~10) by mass, which can effectively improve its compatibility and dispersibility with the epoxy resin, fill the pores of the epoxy resin, make the coating denser, inhibit the penetration of corrosive media in the coating, and effectively enhance the corrosion resistance of the coating.
[0022] Furthermore, in step S3, the ratio of the core-shell composite particle ternary material, curing agent, catalyst and epoxy resin is (3~10):(8~16):(0.02~0.04):(10~20) by mass. First, epoxy resin as a matrix material provides good mechanical properties and chemical stability, and its ratio range ensures the basic performance of the formula; PZ-COFs / corrosion inhibitor@MoS2 ternary nanomaterial enhances the corrosion resistance and self-healing properties of the material; an appropriate amount of curing agent ensures that the epoxy resin can be completely cured under appropriate conditions to form a stable cross-linked network; a small amount of catalyst accelerates the curing reaction, shortens the production cycle, and ensures the uniformity and completeness of the curing reaction; secondly, by adjusting the ratio of each component within a reasonable range, the production cost can be reduced as much as possible while ensuring product performance, which is of great significance for improving the market competitiveness of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 It is a schematic flow chart of a method for preparing an anti-corrosion self-repairing intelligent epoxy composite coating in the present invention; Figure 2 This is a graph showing the particle size test of molybdenum disulfide in the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] like Figure 1 As shown, the present invention discloses a method for preparing an anti-corrosion self-repairing epoxy composite coating, which specifically comprises the following steps: S1: 1,3,5-Tris(4-aminophenyl)benzene (TAPB) and 2,5-dimethoxyterephthalaldehyde (DMTP) were mixed and dispersed in a mixed solution of 1,4-dioxane, n-butanol and methanol in proportion, and dried to obtain a covalent organic framework material (PZ-COFs). Benzotriazole solution (BTA) and covalent organic framework material (PZ-COFs) were dispersed in a solvent in proportion, vacuum loaded, centrifuged, and the centrifuged product was dried to obtain a core-shell composite particle binary material (PZ-COFs / BTA).
[0031] Specifically, weigh 1-2 parts of 1,3,5-tris(4-aminophenyl)benzene and mix with 0.5-1.6 parts of 2,5-dimethoxyterephthalaldehyde, then add 20-100 parts of 1,4-dioxane, 20-100 parts of n-butanol and 0.2-1 parts of methanol to disperse evenly to obtain a uniformly dispersed dispersion. After standing for 20-30 min, slowly drop 0.05-0.25 parts of acetic acid aqueous solution (concentration of 12 mol / L) and adjust the pH value to 4-5. Finally, transfer the mixed solution to a reactor and heat it to 70-80 °C for 24-48 h. After the reaction is completed, the mixture is cooled to room temperature, the product is filtered and washed twice with acetone, and dried in an oven at 60-70 °C for 4-5 h to obtain a covalent organic framework material (PZ-COFs). 0.01-0.1 parts of benzotriazole solution (BTA) and 0.1-5 parts of covalent organic framework material (PZ-COFs) are dispersed in 10-20 parts of water, vacuumed and centrifuged, and the centrifuged product is dried to obtain a core-shell composite particle binary material (PZ-COFs / BTA). In addition, the ratio of the 1,3,5-tris(4-aminophenyl)benzene to 2,5-dimethoxyterephthalaldehyde is preferably (1-5):(1-5) in parts by mass.
[0032] S2: The core-shell composite particle binary material (PZ-COFs / BTA) is dispersed in water, and nano-MoS2 sheets with a diameter of 1000-1500 nm and a thickness of 20-30 nm are added to modify its surface to prepare a core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0033] Specifically, according to the weight percentage, 1 to 10 parts of core-shell type composite particle binary material (PZ-COFs / BTA) are dispersed in 10 to 100 parts of water, and ultrasonically dispersed for 30 to 45 minutes using an ultrasonic cleaner. Then, 1 to 10 parts of nano-MoS2 sheets are added, and the above reaction system is ultrasonicated for 2 to 3 hours, and the reaction is carried out at a constant temperature of 80 to 100 ° C at a speed of 300 to 500 r / min for 24 to 36 hours. Finally, the core-shell type composite particle ternary material (PZ-COFs / BTA@MoS2) is prepared in a vacuum drying oven at 60 ° C.
[0034] S3: The prepared core-shell composite particle ternary material PZ-COFs / BTA@MoS2 is mixed with a curing agent and a catalyst, a small amount of a leveling agent is added, introduced into the epoxy resin, and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0035] Specifically, first, by weight, 10-20 parts of epoxy resin are dispersed in 20-50 parts of ethanol, and then 3-10 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 are added and stirred for 10-40 min. Then, 8-16 parts of curing agent and 0.02-0.04 parts of catalyst are added and stirred evenly to obtain the anti-corrosion self-healing epoxy composite coating, namely PZ-COFs / BTA@MoS2 / EP nanocomposite coating.
[0036] Wherein, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and polyphenol glycidyl ether epoxy resin; The curing agent is one or more of methyltetrahydrophthalic anhydride, polyamide 651, low molecular weight polyamide T31, 1,6-hexanediamine, and maleic anhydride; The catalyst is one or more of tetrabutylammonium chloride, tetrabutylammonium bromide, DMP-30 (2,4,6-tris(dimethylaminomethyl)phenol), and 2-ethyl-4-methylimidazole.
[0037] At the same time, the present invention also provides a method for using the above-mentioned anti-corrosion self-repairing epoxy composite coating, specifically: applying the anti-corrosion self-repairing epoxy composite coating on the surface of a substrate, and forming a PZ-COFs / BTA@MoS2 / EP epoxy coating after curing.
[0038] The substrate may be N80 carbon steel. The coating method may be scraping, and the thickness of the obtained coating is 95-105 μm, preferably 95-100 μm. After curing, an anti-corrosion self-repairing smart epoxy composite coating may be obtained. The curing process adopts gradient heating and is cured in the range of 150-220°C.
[0039] After testing, the epoxy composite coating prepared by the present invention has an adhesion of less than level 1 according to GB / T-9286-2021, a wear resistance strength of greater than 1000HV, and a wear resistance of greater than 5.0L·um -1 In the NaCl solution with a concentration of 3.5 wt.%, the salt spray resistance time is greater than 1400 h. When scratches are made on the surface with a knife, the damaged coating can grow a protective film at the damaged area in 3 to 5 hours, thus completing self-repair. At the same time, after being immersed in the NaCl solution with a concentration of 3.5 wt.% for 900 h, the impedance value at the scratched area of the coating is greater than 1.4×10 9 Ω·cm 2 It can be seen that the epoxy composite coating has excellent corrosion resistance and self-healing properties, and still has good corrosion resistance even under strong acid and alkali conditions (pH range 1~14).
[0040] The present invention also discloses the application of the above-mentioned anti-corrosion self-repairing intelligent epoxy composite coating in pipelines.
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0043] Example 1 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 1 part of 1,3,5-tris(4-aminophenyl)benzene and 0.5 parts of 2,5-dimethoxyterephthalaldehyde, add 20 parts of 1,4-dioxane, 20 parts of n-butanol and 0.2 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 20 minutes, slowly drop 0.05 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 70°C for 24 hours. After the reaction is completed, cool to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 60°C for 4 hours to obtain a covalent organic framework material (PZ-COFs). Disperse 0.01 parts of benzotriazole solution (BTA) and 1 part of covalent organic framework material (PZ-COFs) in 10 parts of water, evacuate the mixture and centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0044] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 7 parts of core-shell composite particle binary material (PZ-COFs / BTA) were dispersed in 70 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 7 parts of nano-MoS2 were added, and the mixture was reacted at 80 °C for 3 hours at a speed of 500 r / min. Finally, the mixture was dried in an oven at 80 °C for 3 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0045] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 10 parts of bisphenol F epoxy resin were dispersed in 20 parts of ethanol by mass, and then 3 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 8 parts of methyltetrahydrophthalic anhydride and 0.02 parts of tetrabutylammonium chloride were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0046] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP smart epoxy coating after curing. The curing process was: 150℃ / 30min+180℃ / 60min+200℃ / 90min.
[0047] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 1 according to GB / T-9286-2021, a wear resistance of 1100 HV, and a wear resistance of 5.1 L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.47×10 9 Ω·cm 2, the salt spray resistance time is 1620 h.
[0048] Example 2 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 2 parts of 1,3,5-tris(4-aminophenyl)benzene and 1.6 parts of 2,5-dimethoxyterephthalaldehyde, add 100 parts of 1,4-dioxane, 100 parts of n-butanol and 1 part of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 30 minutes, slowly drop 0.25 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 80 °C for 48 hours. After the reaction is completed, cool to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 70 °C for 5 hours to obtain a covalent organic framework material (PZ-COFs). Disperse 0.1 parts of benzotriazole solution (BTA) and 5 parts of covalent organic framework material (PZ-COFs) in 20 parts of water, evacuate the mixture, centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0049] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 1 part of core-shell composite particle binary material (PZ-COFs / BTA) was dispersed in 10 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 1 part of nano-MoS2 was added, and the mixture was reacted at 80 °C for 2 hours at a speed of 500 r / min. Finally, the mixture was dried in an oven at 80 °C for 5 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0050] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 10 parts of bisphenol F epoxy resin were dispersed in 20 parts of ethanol by mass, and then 3 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 8 parts of methyltetrahydrophthalic anhydride and 0.02 parts of tetrabutylammonium chloride were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0051] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP smart epoxy coating after curing. The curing process was: 150℃ / 20min+180℃ / 80min+200℃ / 80min.
[0052] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 0 according to GB / T-9286-2021, a wear resistance of 1054HV, and a wear resistance of 5.2L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.50×10 9 Ω·cm 2 , the salt spray resistance time is 1540 h.
[0053] Example 3 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 1.8 parts of 1,3,5-tris(4-aminophenyl)benzene and 1.4 parts of 2,5-dimethoxyterephthalaldehyde, mix them, add 40 parts of 1,4-dioxane, 60 parts of n-butanol and 0.7 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 25 minutes, slowly drop 0.2 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 75°C for 36 hours. After the reaction is completed, cool it to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 65°C for 4-5 hours to obtain a covalent organic framework material (PZ-COFs). Disperse 0.08 parts of benzotriazole solution (BTA) and 3 parts of covalent organic framework material (PZ-COFs) in 10-20 parts of water, evacuate the mixture, centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0054] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 10 parts of core-shell composite particle binary material (PZ-COFs / BTA) were dispersed in 100 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 10 parts of nano-MoS2 were added, and the reaction was carried out at 80 °C for 3 hours at a speed of 300 r / min. Finally, the mixture was dried in an oven at 80 °C for 4 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0055] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 10 parts of bisphenol F epoxy resin were dispersed in 25 parts of ethanol by mass, and then 4 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 8 parts of maleic anhydride and 0.02 parts of tetrabutylammonium bromide were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0056] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP smart epoxy coating after curing. The curing process was: 150℃ / 30min+190℃ / 80min+220℃ / 70min.
[0057] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 1 according to GB / T-9286-2021, a wear resistance of 1120HV, and a wear resistance of 5.0L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.58×10 9 Ω·cm 2 , the salt spray resistance time is 1750 h.
[0058] Example 4 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 1.4 parts of 1,3,5-tris(4-aminophenyl)benzene and 1.1 parts of 2,5-dimethoxyterephthalaldehyde, mix them, add 40 parts of 1,4-dioxane, 40 parts of n-butanol and 0.5 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 20 min, slowly drop 0.1 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 70°C for 24 hours. After the reaction is completed, cool it to room temperature, filter the product, wash it with acetone twice, and dry it in a 70°C oven for 4 hours to obtain a covalent organic framework material (PZ-COFs). Disperse 0.08 parts of benzotriazole solution (BTA) and 3 parts of covalent organic framework material (PZ-COFs) in 10 parts of water, evacuate the mixture and centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0059] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 Four parts of core-shell composite particle binary material (PZ-COFs / BTA) were dispersed in 50 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 3 parts of nano-MoS2 were added, and the mixture was reacted at 80 °C for 3 hours at a speed of 300-500 r / min. Finally, the mixture was dried in an oven at 80 °C for 3-5 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0060] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 20 parts of polyphenol glycidyl ether epoxy resin were dispersed in 40 parts of ethanol, and then 10 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 9 parts of 1,6-hexanediamine and 0.02 parts of tetrabutylammonium bromide were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0061] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP epoxy coating after curing. The curing process was: 160℃ / 60min+190℃ / 60min+220℃ / 30min.
[0062] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 1 according to GB / T-9286-2021, a wear resistance strength of 1000HV, and a wear resistance of 5.0L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.57×10 9 Ω·cm 2 , the salt spray resistance time is 1710 h.
[0063] Example 5 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 1 part of 1,3,5-tris(4-aminophenyl)benzene and 0.8 parts of 2,5-dimethoxyterephthalaldehyde, add 70 parts of 1,4-dioxane, 70 parts of n-butanol and 0.5 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 20-30 min, slowly drop 0.25 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 80 °C for 28 hours. After the reaction is completed, cool to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 60 °C for 4-5 hours to obtain a covalent organic framework material (PZ-COFs). Disperse 0.08 parts of benzotriazole solution (BTA) and 4 parts of covalent organic framework material (PZ-COFs) in 20 parts of water, evacuate the mixture, centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0064] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 1 part of core-shell composite particle binary material (PZ-COFs / BTA) was dispersed in 30 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 1 part of nano-MoS2 was added, and the reaction was carried out at 80 °C at a speed of 500 r / min for 2 hours. Finally, the reaction was carried out in an oven at 80 °C for 3 to 5 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0065] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 10 parts of polyphenol glycidyl ether epoxy resin were dispersed in 20 parts of ethanol, and then 5 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 8 parts of methyltetrahydrophthalic anhydride and 0.03 parts of 2-ethyl-4-methylimidazole were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0066] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP epoxy coating after curing. The curing process was: 150℃ / 30min+180℃ / 60min+220℃ / 90min.
[0067] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 0 according to GB / T-9286-2021, a wear resistance of 1200 HV, and a wear resistance of 5.4 L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.60×10 9 Ω·cm 2 , the salt spray resistance time is 1820 h.
[0068] Example 6 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 2 parts of 1,3,5-tris(4-aminophenyl)benzene and 1.6 parts of 2,5-dimethoxyterephthalaldehyde, add 50 parts of 1,4-dioxane, 50 parts of n-butanol and 0.4 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 20-30 min, slowly drop 0.08 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 78 °C for 24 h. After the reaction is completed, cool to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 65 °C for 4 h to obtain a covalent organic framework material (PZ-COFs). Disperse 0.06 parts of benzotriazole solution (BTA) and 2 parts of covalent organic framework material (PZ-COFs) in 20 parts of water, evacuate the mixture, centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0069] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 Three parts of core-shell composite particle binary material (PZ-COFs / BTA) were dispersed in 70 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 1 part of nano-MoS2 was added, and the reaction was carried out at 80 °C for 2 hours at a speed of 400 r / min. Finally, the mixture was dried in an oven at 80 °C for 4 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0070] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 20 parts of bisphenol A epoxy resin were dispersed in 50 parts of ethanol by mass, and then 10 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 40 min. Then, 15 parts of low molecular weight polyamide T31 and 0.04 parts of tetrabutylammonium bromide were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0071] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP epoxy coating after curing. The curing process was: 150℃ / 30min+160℃ / 90min+229℃ / 30min.
[0072] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 0 according to GB / T-9286-2021, a wear resistance of 1180HV, and a wear resistance of 5.4L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.40×10 9 Ω·cm 2, the salt spray resistance time is 1400 h.
[0073] Example 7 A method for preparing an anti-corrosion self-repairing epoxy composite coating comprises the following steps: 1) Preparation of core-shell composite particle binary materials (PZ-COFs / BTA) Weigh 1.2 parts of 1,3,5-tris(4-aminophenyl)benzene and 0.8 parts of 2,5-dimethoxyterephthalaldehyde, mix them, add 100 parts of 1,4-dioxane, 100 parts of n-butanol and 0.9 parts of methanol and disperse them evenly to obtain a uniformly dispersed dispersion. After standing for 30 min, slowly drop 0.05 parts of acetic acid aqueous solution (concentration of 12 mol / L). Finally, transfer the mixed solution to a reactor and heat it to 80 °C for 48 h. After the reaction is completed, cool it to room temperature, filter the product, wash it with acetone twice, and dry it in an oven at 60 °C for 5 h to obtain a covalent organic framework material (PZ-COFs). Disperse 0.06 parts of benzotriazole solution (BTA) and 3 parts of covalent organic framework material (PZ-COFs) in 15 parts of water, evacuate the mixture, centrifuge it, and dry it to obtain a shell-type composite particle binary material (PZ-COFs / BTA).
[0074] 2) Preparation of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 2 parts of core-shell composite particle binary material (PZ-COFs / BTA) were dispersed in 50 parts of water, and ultrasonically dispersed for 2 hours using an ultrasonic cleaner. Then, 5 parts of nano-MoS2 were added, and the reaction was carried out at 80 °C for 2 hours at a speed of 400 r / min. Finally, the reaction was carried out in an oven at 80 °C for 3 to 5 hours to prepare the core-shell composite particle ternary material PZ-COFs / BTA@MoS2.
[0075] 3) Preparation of anti-corrosion self-repairing epoxy composite coating First, 15 parts of bisphenol A epoxy resin were dispersed in 30 parts of ethanol by mass, and then 3 parts of core-shell composite particle ternary material PZ-COFs / BTA@MoS2 were added and stirred for 10 min. Then, 8 parts of methyltetrahydrophthalic anhydride and 0.02 parts of 2-ethyl-4-methylimidazole were added and stirred evenly to obtain an anti-corrosion self-healing epoxy composite coating.
[0076] The anti-corrosion self-repairing epoxy composite coating was applied to the surface of N80 carbon steel and formed into a PZ-COFs / BTA@MoS2 / EP epoxy coating after curing. The curing process was: 150℃ / 30min+170℃ / 50min+200℃ / 60min.
[0077] The anti-corrosion self-repairing smart epoxy composite coating prepared in this embodiment has an adhesion of level 0 according to GB / T-9286-2021, a wear resistance strength of 1040HV, and a wear resistance of 5.1L·um -1 At the same time, after immersion in 3.5 wt.% NaCl solution for 900 h, the impedance value of the coating scratch was 1.49×10 9 Ω·cm 2 , the salt spray resistance time is 1530 h.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an anti-corrosion self-repairing epoxy composite coating, characterized in that: The following steps are involved: S1: adding 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to a mixed solution of 1,4-dioxane, n-butanol and methanol, and reacting to obtain a covalent organic framework material; dispersing a benzotriazole solution and the covalent organic framework material into a solvent, vacuum loading, and centrifuging to obtain a core-shell composite particle binary material; S2: dispersing the core-shell composite particle binary material in water, adding nano-MoS2 sheets to modify its surface, and preparing a core-shell composite particle ternary material; S3: Mix the core-shell composite particle ternary material with a curing agent and a catalyst, add the mixture into epoxy resin, stir evenly, and obtain the anti-corrosion self-repairing epoxy composite coating.
2. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S1, the ratio of 1,3,5-tris(4-aminophenyl)benzene to 2,5-dimethoxyterephthalaldehyde is (1-2):(0.5-1.6) by mass.
3. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S1, the ratio of 1,4-dioxane, n-butanol and methanol is (20-100):(20-100):(0.2-1) by mass.
4. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: The cavity diameter of the covalent organic framework material is 450-1300 nm, and the surface pore diameter is 2-26.5 nm.
5. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S1, the ratio of the benzotriazole solution to the covalent organic framework material is (0.01-0.1):(0.1-5) by weight.
6. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S2, the diameter of the nano MoS2 sheet is 1000-1500 nm and the thickness is 20-30 nm.
7. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S2, the ratio of the nano-MoS2 sheets to the core-shell composite particle binary material is (1-10):(1-10) by mass.
8. The method for preparing an anti-corrosion self-repairing epoxy composite coating according to claim 1, characterized in that: In step S3, the ratio of the core-shell composite particle ternary material, the curing agent, the catalyst and the epoxy resin is (3-10):(8-16):(0.02-0.04):(10-20) by mass.
9. An anti-corrosion self-repairing epoxy composite coating, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. An anti-corrosion self-repairing epoxy composite coating, characterized in that: The anti-corrosion self-repairing epoxy composite coating described in claim 8 is coated on the surface of the substrate and cured to obtain the anti-corrosion self-repairing epoxy composite coating; the thickness of the anti-corrosion self-repairing epoxy composite coating is 95-105 μm; the adhesion of the anti-corrosion self-repairing epoxy composite coating is less than level 1, the wear resistance strength is greater than 1000 HV, and the wear resistance is greater than 5.0 L·um -1 In a NaCl concentration of 3.5 wt.%, the salt spray resistance time is greater than 1400 h, and the self-repairing efficiency of the anti-corrosion self-repairing epoxy composite coating is greater than 90%.
Citation Information
Patent Citations
Anticorrosive polyurea coating for petrochemical industry and preparation method thereof
CN112480797A
Composite aluminum pipe G-shaped pipe and machining process thereof
CN114133838A
Self-healing coating based on covalent organic framework material and preparation method thereof
CN114539870A